Upaya Peningkatan Kemampuan Bahasa Inggris Menggunakan Lagu Barat Pada Mahasiswa Farmasi - Utomo, Slamet (Universitas Muria Kudus, 2025)
English language skills can be done in various ways, one of which is by using western song media that can be applied in everyday life. In this study, the author aims to determine whether there is an influence of western songs in improving english language skills in Pharmacy students at STIKES Kendal. The type of research used in this study is quantitative with a cross-sectional research design. The study was conducted on Pharmacy students at STIKES Kendal with a diploma level of three in the even semester of 2024/2025. Based on the research results obtained from research respondents, it is known that listening to western songs can improve english listening, pronunciation and vocabulary skills in Pharmacy students at STIKES Kendal.